Hans Jonas and Vasily Grossman: Reflections on the Human Condition after Auschwitz - Tibaldeo, Roberto Franzini (ETHICS IN PROGRESS, 2014)
The article endeavours to compare the reflections on the Shoah of two of the most celebrated intellectuals of Jewish origin of the 20th century, namely the German philosopher Hans Jonas (1903-1993) and the Soviet writer Vasily Grossman (1905-1964). Both Jonas’ essay on The Concept of God after Auschwitz (1987) and Grossman’s novels and reports, such as The Hell of Treblinka (1944), Life and Fate (1980), and The Sistine Madonna (1989), are characterised by a thorough enquiry into the ambivalence of the human condition, that tries to shed some light on the disturbing abyss of Auschwitz and the Shoah. Although neither Jonas nor Grossman considered themselves as religious believers, thanks to the Shoah they recollected their Jewish roots and developed peculiar and innovative thoughts on the meaning and vulnerability of life, human freedom, immortality, and God. The article endeavours to highlight the main similarities and differences between these two authors, who tackled the issue of thinking after Auschwitz.